Pertumbuhan Penduduk dan Dampaknya terhadap Pengangguran di Banten - Maulana Alif; Saepul Ajril; Akrom (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the causal relationship between rapid population growth and the increasing unemployment rate in Banten Province, as well as to identify the main obstacles that exacerbate this problem and formulate comprehensive handling strategies. Using a library research method with a qualitative approach, this study examines various secondary data sources from BPS Banten, scientific journals, government policy reports, and related literature over the past decade. The results show that high birth rates and uncontrolled urbanization have created a labor force surplus that is unbalanced with the expansion of employment opportunities, compounded by the skills gap between educational graduates and the needs of modern industry, as well as socio-cultural barriers and weak policy governance. This study concludes that an integrated strategy encompassing demographic control, vocational education reform, economic diversification, strengthening institutional coordination, and socio-cultural transformation is urgently needed to transform demographic pressure into a productive demographic dividend for Banten.